How to start a dragon academy - David, Erica (New York : Simon Spotlight, 2014)
Hiccup must find a way to show the Vikings of Berk how helpful the dragons can be.
3.2
K-3
Keywords: Haddock, Hiccup Horrendous, III (Fictitious character) -- Juvenile fiction; Dragons -- Juvenile fiction; Vikings -- Juvenile fiction; Haddock, Hiccup Horrendous, III (Fictitious character) -- Fiction; Dragons -- Fiction; Vikings -- Fiction